Leader-versus-member and fair-versus-biased categorisations as safeguards against negative effects of demographic diversity on group attraction - Ramadhar Singh; Naureen Bhullar; Krithiga Sankaran (IIMB Management Review, 2019)
How leadership and fairness can safeguard against negative effects of demographic diversity on group attraction was investigated. When the race of the leader and the member of a group were manipulated, categorisation by race of the former was more important than that of the latter. Also, both the in-group preference and the out-group derogation characterised group attraction. The fair reputation of the leader reduced the difference between the in-group and out-group categorisation more than the biased reputation did. Apparently, the leadership and fairness categorisations can be effective safeguards against negative consequences of demographic diversity on group attraction in modern organisations. Keywords: Fair leader, Information integration, Social identity, Racial diversity